2019
DOI: 10.1016/j.atherosclerosis.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Translocator protein localises to CD11b+ macrophages in atherosclerosis

Abstract: Background: Atherosclerosis is characterized by lipid deposition, monocyte infiltration and foam cell formation in the artery wall. Translocator protein (TSPO) is abundantly expressed in lipid rich tissues. Recently, TSPO has been identified as a potential diagnostic tool in cardiovascular disease. The purpose of this study was to determine if the TSPO ligand, 18 F-PBR111, can identify early atherosclerotic lesions and if TSPO expression can be used to identify distinct macrophage populations during lesion pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Macrophages promote invasion and metastasis from primary tumor sites by allowing cancer cells to engage in an autocrine loop that promotes cancer cell migration. Here, we evaluated the levels of the macrophage marker CD11b in various organs after injection of conditioned medium [ 59 , 60 ]. After injecting the conditioned medium into healthy mice, macrophage markers were upregulated in all of the major organs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages promote invasion and metastasis from primary tumor sites by allowing cancer cells to engage in an autocrine loop that promotes cancer cell migration. Here, we evaluated the levels of the macrophage marker CD11b in various organs after injection of conditioned medium [ 59 , 60 ]. After injecting the conditioned medium into healthy mice, macrophage markers were upregulated in all of the major organs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As atherosclerosis progresses, the arterial wall thickens with lipid deposits, monocyte infiltration, and foam cell formation. Previous studies conducted using the translocator protein demonstrated that CD11b + macrophages, rather than tissue-resident F4/80 + macrophages, were predominant in atherosclerotic lesions [ 29 ]. Evidence confirms that in the inflammatory microenvironment, activated platelets can skew monocytes in a cell-contact-dependent manner through the GPIb-CD11b axis [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may not, however, preclude the presence of more subtle hepatocyte injury and liver inflammation; other possible mechanisms possibly contributing to the apparent systemic inflammation provoked by high sucrose diet include high fructose induced-elevated blood pressure, elevated serum triglycerides, or insulin and leptin resistance, which we did not assess in this study. Furthermore, the parallel increases in WBC counts and upregulated microglial markers may reflect the distinction between the metabolic effects of dietary sucrose and obesity per se, which may preferentially activate inflammatory processes in peripheral tissues 10,11 . Moreover, high-sucrose diets are known to lead to gastrointestinal dysbiosis, which can manifest as central and peripheral inflammation 47,48 or can indirectly inhibit glutamine synthetase activity in peripheral and central immune cells 49,50 to contribute to widespread inflammation.…”
Section: Discussionmentioning
confidence: 99%